2007
DOI: 10.1523/jneurosci.1602-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Disruption of Protein Kinase A Anchoring Reveals a Role for Compartmentalized Kinase Signaling in Theta-Burst Long-Term Potentiation and Spatial Memory

Abstract: Studies of hippocampal long-term potentiation (LTP), a cellular model of memory storage, implicate cAMP-dependent protein kinase (PKA) in presynaptic and postsynaptic mechanisms of LTP. The anchoring of PKA to AKAPs (A kinase-anchoring proteins) creates compartmentalized pools of PKA, but the roles of presynaptically and postsynaptically anchored forms of PKA in late-phase LTP are unclear. In this study, we have created genetically modified mice that conditionally express Ht31, an inhibitor of PKA anchoring, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 49 publications
(84 reference statements)
4
66
0
2
Order By: Relevance
“…8). Phosphorylation and targeting of GluA1-containing AMPARs by PKA is facilitated by the anchoring protein AKAP and disruption of the PKA-AKAP interaction has previously been shown to impede LTP and spatial learning (1,2,4). We found that the PKA RII subunit binds to AKAP as early as 15 min after conditioning onset and that disruption of this interaction by the Ht31 peptide results in inhibition of conditioning (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…8). Phosphorylation and targeting of GluA1-containing AMPARs by PKA is facilitated by the anchoring protein AKAP and disruption of the PKA-AKAP interaction has previously been shown to impede LTP and spatial learning (1,2,4). We found that the PKA RII subunit binds to AKAP as early as 15 min after conditioning onset and that disruption of this interaction by the Ht31 peptide results in inhibition of conditioning (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Intracellular compartmentalization by scaffolding proteins serves to maintain the functional specificity of multiple signaling pathways. Protein kinase A-anchoring proteins (AKAPs) target PKA to distinct subcellular loci and regulate AMPAR surface expression and synaptic plasticity (1)(2)(3)(4). Kinase suppressor of Ras1 (KSR1), in contrast, is a scaffold for the Ras/MEK/ERK cascade that facilitates PKC-coupled activation of ERK required for plasticity and memory formation (5).…”
mentioning
confidence: 99%
“…Higher theta-range frequencies may dominate in wakeful animals, or during learning, since recent studies in awake, behaving subjects indicate that learning-related theta centers around 7-11 Hz in dorsal striatum (DeCoteau et al 2007;Tort et al 2008). Nonetheless, we initially used 5-Hz because 5-Hz TBS evokes robust LTP in hippocampal slice Nie et al 2007), and striatal STDP pairings paced at 5 Hz evoke LTP in young animals (Shen et al 2008). While 5 Hz indeed evoked a modest LTP, we found the amplitude and duration were greatly improved by using higher frequency theta-bursts.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The pharmacological inhibition of PKA anchoring also blocked the late phase LTP and synaptic capture, suggesting that spatial compartmentalization of PKA signaling via binding to A kinase-anchoring proteins (AKAPs) is critical in these processes (Huang et al, 2006;Nie et al, 2007). (4) This pharmacological evidence received further support from experiments with transgenic mice that have genetically reduced PKA activity and display impaired synaptic capture of L-LTP (Young et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%